2007
DOI: 10.1016/j.jcorpfin.2007.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Author Affiliation Index, finance journal ranking, and the pattern of authorship

Abstract: ________________________________________________________________________

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
76
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 12 publications
5
76
0
6
Order By: Relevance
“…Notably, while the business domains of the studies described are diverse and the study methods utilized are varied, most of these journal ranking studies had a conclusion in common: the studies essentially confirmed the status quo rank of the top journals in their respective fields (Chen and Huang 2007;Harris 2008;Lowry et al 2013;Oltheten et al 2005;Peffers and Ya 2003;Polonsky and Whitelaw 2006). Perhaps this finding is not surprising; the most prestigious journals in a domain may be considered the most prestigious because that ranking may be, to a large degree, deserved and consistently confirmed by journal ranking studies.…”
Section: Previous Ranking Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Notably, while the business domains of the studies described are diverse and the study methods utilized are varied, most of these journal ranking studies had a conclusion in common: the studies essentially confirmed the status quo rank of the top journals in their respective fields (Chen and Huang 2007;Harris 2008;Lowry et al 2013;Oltheten et al 2005;Peffers and Ya 2003;Polonsky and Whitelaw 2006). Perhaps this finding is not surprising; the most prestigious journals in a domain may be considered the most prestigious because that ranking may be, to a large degree, deserved and consistently confirmed by journal ranking studies.…”
Section: Previous Ranking Studiesmentioning
confidence: 91%
“…In finance, Oltheten et al (2005) conducted a perception study of finance academicians to rank finance journals and considered the effects of researcher geographic origin, seniority, and journal affiliation. Another ranking of finance journals was generated by Chen and Huang (2007) who ranked journals in that domain through use of the ratio of articles authored by faculty of an identified pool of universities to the total of articles authored by all authors. In the information systems (IS) domain, Peffers and Ya (2003) conducted an online perceptions survey of IS academicians and utilized the results to rank journals.…”
Section: Previous Ranking Studiesmentioning
confidence: 99%
“…However, the downside of impact factor analysis includes self-citation bias and sociological and statistical factors (Amin & Mabe, 2000). While a subjective evaluation method is an alternative, it has the drawbacks of being self-serving and prone to predisposition bias and slow-fading memory bias (Chen & Huang, 2007, Kim, Morse, & Zingales, 2009. As mentioned in Beattie and Goodacre (2006), all existing finance journal evaluation methods have inherent limitations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research methods such as citation analysis, co-authorship analysis, affiliation analysis, and co-word analysis have been used in order to identify interdisciplinary characteristics in various domains. In particular, since authors from a wide variety of disciplinary domains can be considered as a certain level of interdisciplinarity, affiliation information of authors has been approached in terms of analyzing the interdisciplinary domains and identifying the interdisciplinarity of digital libraries (Chen & Huang 2007;Cronin & Meho 2008).…”
Section: Introductionmentioning
confidence: 99%